Simultaneous Estimation of Intake and Residual Mass Using In-Cylinder Pressure in an Engine with Negative Valve Overlap. Issue 11 (2016) - Guardiola, C.; Triantopoulos, V.; Bares, P.; Bohac, S.; Stefanopoulou, A.
Abstract: This work presents a new method for the simultaneous estimation of the intake and residual mass in an engine operating with negative valve overlap. The method exclusively uses the in-cylinder pressure information and no additional measurement is needed. It is based on the determination of the total mass through the pressure resonance in the cylinder and the assumption of a polytropic expansion of the gas during the exhaust stroke for determining the residual gases. The method has been demonstrated on an engine with negative valve overlap operating in SI, SACI and HCCI combustion. The results show that the proposed method can provide good mass estimations in most cycles in HCCI and SACI combustion, and in lightly knocking cycles while operating in SI combustion.